Pengaruh Pendidikan Islam terhadap Keputusan Generasi Z dalam Berwirausaha: Analisis Maqashid Syariah - Musyafa', Musyafa'; Chofifah, Lailatul; Aminnudin, Moch (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the influence of Islamic education on Generation Z's entrepreneurial decisions from the perspective of maqashid syariah. The research employs a quantitative methodology by collecting data through questionnaires distributed to Generation Z in Jepara, using the Slovin formula for sample determination and the Likert scale for data measurement. Statistical analysis was conducted to obtain a descriptive overview of the results, which were then analyzed based on maqashid syariah. The findings indicate that Islamic education significantly influences entrepreneurial decisions, particularly in safeguarding religion (hifz din) and wealth (hifz mal), thus encouraging the formation of ethical and socially responsible entrepreneurs. This demonstrates that entrepreneurship in Islam is not merely aimed at achieving material gains but also at attaining holistic community welfare in line with maqashid syariah principles.